1999
DOI: 10.1542/peds.103.5.e68
|View full text |Cite
|
Sign up to set email alerts
|

Differential Calming Responses to Sucrose Taste in Crying Infants With and Without Colic

Abstract: As in newborns, a significant calming effect of sucrose taste that persisted beyond the cessation of mouthing could be elicited in crying 6-week-old infants, but it required a stronger taste stimulus to do so. As predicted, infants with colic were less effectively calmed by sucrose taste than infants without. These differential effects could not be accounted for by differences in crying when the stimulus was applied or by differences in mouthing behavior. Before a feed, these differences in calming were specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 49 publications
3
33
0
2
Order By: Relevance
“…40 Numerous subsequent studies reported the same findings. [41][42][43][44][45][46][47] Calming effects were clearly nonsedating, with infants remaining alert after sucrose administration. 19 In addition, effects were observed to be sweet-taste dependent, sucrose was more effective than glucose, and the least sweet sugar, lactose, was no more effective than water in reducing crying.…”
Section: Human Model Studiesmentioning
confidence: 96%
“…40 Numerous subsequent studies reported the same findings. [41][42][43][44][45][46][47] Calming effects were clearly nonsedating, with infants remaining alert after sucrose administration. 19 In addition, effects were observed to be sweet-taste dependent, sucrose was more effective than glucose, and the least sweet sugar, lactose, was no more effective than water in reducing crying.…”
Section: Human Model Studiesmentioning
confidence: 96%
“…Infants who cry more persistently differ from those who cry less in that they have a higher crying-to-fussing ratio (suggesting greater intensity). In addition, according to Barr et al, infants with colic were found to be less likely to be placated by an orally administered sucrose solution than infants without colic [12].…”
Section: Common Physiological and Behavioral Problemsmentioning
confidence: 99%
“…Generally, the direct causes were incompletely understood, but it has been assumed that it is imputed to different contributors such as central nervous system pathway disturbance, inconvenient infant-family relationship, parental anxiety, and different gastrointestinal pathologies like cow's milk allergy, gastroesophegeal reflux or motility disorders. [12][13][14][15][16] Moreover, altered micro-biota theory is also suggested to affect gut motility and gas production, leading to the colicky episodes. 17 There was old concept linked to breastfeeding influential effect against infantile colic, but recently one study rejects this concept and proved that breastfeeding did not have a protective effect on the development of colic.…”
Section: Causes Of Infantile Colicmentioning
confidence: 99%